Injuries in Swedish elite football - a prospective study on injury definitions, risk for injury and injury pattern during 2001 - Walden, M.; Hägglund, M.; Ekstrand, J. (Scandinavian Journal of Medicine & Science in Sports, 2005)
The purpose of this study was to study the risk for injury and injury pattern in Swedish male elite football and to compare two different injury definitions. A prospective cohort study was conducted during 2001 on all 14 teams (310 players) in the Swedish top division. Injuries and individual exposure were recorded. Injury was defined as time-lost injury (715 injuries) and for comparison as tissue injury (765 injuries). No significant difference in the risk for injury between tissue injuries and time-lost injuries was found during matches (27.2 vs. 25.9 injuries per 1000 match hours, P=0.66) or training sessions (5.7 vs. 5.2 injuries per 1000 training hours, P=0.65). The risk for injury during training was significantly higher during the pre-season compared with the competitive season (P=0.01).